Transcriptional analysis implicates endoplasmic reticulum stress in bovine spongiform encephalopathy - Tang, Yue; Xiang, Wei; Terry, Linda; Kretzschmar, Hans A.; Windl, Otto (PLoS ONE, 2010)
Bovine spongiform encephalopathy (BSE) is a fatal, transmissible, neurodegenerative disease of cattle. To date, the disease process is still poorly understood. In this study, brain tissue samples from animals naturally infected with BSE were analysed to identify differentially regulated genes using Affymetrix GeneChip Bovine Genome Arrays. A total of 230 genes were shown to be differentially regulated and many of these genes encode proteins involved in immune response, apoptosis, cell adhesion, stress response and transcription. Seventeen genes are associated with the endoplasmic reticulum (ER) and 10 of these 17 genes are involved in stress related responses including ER chaperones, Grp94 and Grp170. Western blotting analysis showed that another ER chaperone, Grp78, was up-regulated in BSE. Up-regulation of these three chaperones strongly suggests the presence of ER stress and the activation of the unfolded protein response (UPR) in BSE. The occurrence of ER stress was also supported by changes in gene expression for cytosolic proteins, such as the chaperone pair of Hsp70 and DnaJ. Many genes associated with the ubiquitin-proteasome pathway and the autophagy-lysosome system were differentially regulated, indicating that both pathways might be activated in response to ER stress. A model is presented to explain the mechanisms of prion neurotoxicity using these ER stress related responses. Clustering analysis showed that the differently regulated genes found from the naturally infected BSE cases could be used to predict the infectious status of the samples experimentally infected with BSE from the previous study and vice versa. Proof-of-principle gene expression biomarkers were found to represent BSE using 10 genes with 94% sensitivity and 87% specificity. © 2010 Tang et al.
CRIS-Team Scopus Importer:2021-08-17